Elder Abuse and Neglect in China: Prevalence, Co-occurrence, and Intergenerational Risk Factors - Chen, Mengtong (Journal of interpersonal violence, 2022)
The prevalence and patterns of elder abuse and neglect in China have been understudied. The objectives of this study were to examine the chronicity and prevalence of different patterns of elder abuse, and the influence of individual and contextual risk factors. We used data from a sample of 7,466 adults randomly recruited from six regions in China. The participants responded to a questionnaire about their demographic characteristics, childhood abuse experiences, and instances of abuse and neglect against their elderly parents. Logistic regression analysis was performed to examine the association of elder abuse and neglect with individual and contextual factors. The results showed that one in 10 participants reported that their elderly parents had experienced abuse or neglect in the past year. The elder victims were reported to have suffered different types of abuse and neglect on multiple occasions, ranging from 3.6 to 11.82 times on average. More than 5% of participants reported that their elderly parents had suffered two or more types of abuse and neglect in the past year, accounting for 40% of the elderly victims. The co-occurrence of elder abuse within elderly couples was also high. Reports of abuse and neglect of elderly parents were related to low socioeconomic status, living in rural areas, and the experience of childhood abuse of the participants. This study supports the model of intergenerational transmission of violence in the Chinese population. The high prevalence, chronicity, and co-occurrence of elder abuse and neglect underline the importance of screening for risk factors, and have implications for preventive practice and policy.